Credit cycles: Experimental evidence - Baptiste Massenot (Leibniz Institute for Financial Research SAFE, 2020)
Credit boom-busts are observed in experimental credit markets with perfect information, no aggregate shocks, and no speculative motive. By contrast, a stable outcome is observed in the island economy, which isolates the borrowers but is otherwise similar to the market economy. The higher willingness to pay for credit following higher market but not island interest rates is consistent with herding, which can create spiraling effects and predict a credit boom-bust.
Keywords: 330